Evidence for the Involvement of Cytokines Modulation and Prokinetic Properties in Gastric Ulcer Healing Effects of Helicteres sacarolha A. St.‐Hil. A. Juss. Issue 12 (11th November 2022) - Olaitan Balogun, Sikiru; Sabino Damazo, Amilcar; Pavan, Eduarda; de Freitas Figueiredo, Fabiana; Arunachalam, Karuppusamy; de Souza Mesquita, Leonardo M.; Vilegas, Wagner; Tabajara de Oliveira Martins, Domingos
Abstract: Preparations of Helicteres sacarolha (Malvaceae) leaves and roots are used in the form of decoction, infusion or maceration, to treat gastrointestinal disturbances, among others. Studies supporting some of its ethnomedicinal uses are still incipient. The present study aimed to investigate it potential effect on chronic ulcer, ulcerative colitis and possible prokinetic activities as part of its mechanism of action. The powdered leaves of Helicteres sacarolha (HEHs) was prepared by maceration in 70 % hydroethanolic solution. Its qualitative phytochemical constituents were investigated by direct flow injection analysis coupled to atmospheric pressure chemical ionization ion trap tandem mass spectrometry (FIA‐APCI‐IT‐MS n ). The gastric ulcer healing effect was evaluated in acetic acid induced chronic ulcer in mice and the lesions were evaluated, including analysis of blood plasma cytokine levels. The prokinetic properties (gastric emptying and intestinal transit) were carried out in mice. Potential anti‐ulcerative colitis activity was evaluated in rats using 2, 4, 6‐trinitrobenzenesulfonic acid (5 % TNBS) ‐induced colitis. All animal experiments were carried out at the doses of 20, 50 and 250 mg/kg (p.o.). Eight compounds were putatively identified, specifically lariciresinol, and its derivatives, kaempferol derivatives and Tricin‐ O ‐Glc. The extract promoted increased gastric ulcer healing at all doses tested. Modulation of the cytokines involved inhibition of some key pro‐inflammatory cytokines with maximum effect on IL‐1β (70 %, 50 mg/kg, p <0.05), TNF‐α (79 %, 20 mg/kg, p <0.01), and in the anti‐inflammatory cytokines, namely IL‐10 (57 %, 50 mg/kg, p <0.05) and IL‐17 (79 %, only at 50 mg/kg, p <0.05). Histological findings demonstrated a mitigated inflammatory activity, and tissues undergoing regeneration. HEHs treatment caused delayed gastric emptying, and increased intestinal transit, but had no effect in the experimentally induced ulcerative colitis. We report for the first time putatively the presence of Lariciresinol and tricin derivatives from the hydroethanolic leaves extract of H. sacarolha . Its possible mechanism of actions of gastric ulcer healing involves cytokines modulation, mitigation of inflammatory response and tissue regeneration and provoked opposing effect in the gastrointestinal system. The present study demonstrates the therapeutic potential of H. sacarolha leaves used in Brazilian ethnomedicine in the treatment of chronic gastric ulcer. Abstract :